Надання електронних адміністративних послуг - Васюта, Тетяна; Саврук, Леся (Видавництво Львівської політехніки, 2016)
The article highlights the importance of investigation scientific and normative-legal approaches to understanding concept ‘admistrative service’. Also was considered cardinal problems of rendering administrative services witch have to be solved.
Keywords: послуги; адміністративна послуга; електронні послуги